Effect of pre-harvest spray of calcium nitrate, boric acid and zinc sulphate on yield and quality of Nagpur mandarin (Citrus reticulata Blanco) - Meena, M. K.; Jain, M. C.; Singh, J.; Sharma, M.; Shing, B.; Maurya, I. B. (International Journal of Horticultural Science, 2016)
An investigation was conducted on uniform, healthy, eight year old trees of Nagpur mandarin (citrus reticulata Blanco) at Fruit Research Farm, Department of Fruit Science at College of Horticulture and Forestry, Jhalawar during 16 September, 2014 to 1 March, 2015. Various doses of calcium nitrate (1.0%, 2.0% and 3.0 %), boric acid (0.2 %, 0.4 % and 0.6 %) and zinc sulphate (0.2 %, 0.4 % and 0.6 %) were sprayed before harvesting and compared with untreated ones. The results obtained indicated that the trees sprayed with T27 i.e. (calcium nitrate 3.0 % + boric acid 0.6 % + zinc sulphate 0.6 %) showed maximum increase diameter of fruit, fruit weight, fruit volume, number of fruits per plant, fruit yield per plant, estimated yield per hectare, reducing sugar, non reducing sugar, total sugar, juice per cent, sensory score and reduced peel thickness over control. Further, T24 treatment combination (calcium nitrate 3.0 % + boric acid 0.4 % + zinc sulphate 0.6 %) has also significantly increased number of segments per fruit, TSS, TSS: Acid ratio, ascorbic acid content, and reduced number of seeds per fruit and acidity percent of fruits.